2007
DOI: 10.1093/jn/137.4.973
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Docosahexaenoic Acid Lowers Diastolic Blood Pressure in Middle-Aged Men and Women1

Abstract: The intake of (n-3) long-chain PUFA is associated with a decreased risk of fatal myocardial infarction. Whether this effect is attributable to the effects of docosahexaenoic acid [22:6(n-3) (DHA)] on vascular function, particularly at intakes <1 g/d, is unknown. We report a randomized, double-blind, crossover, placebo controlled trial of 0.7 g DHA/d as a purified algal derived triacylglycerol (1.5 g/d) vs. placebo (1.5 g olive oil/d) on vascular function and biochemical indices of endothelial dysfunction in 38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 29 publications
3
50
0
7
Order By: Relevance
“…About one-fifth of the study population was nonwhite, with similar proportions of Asian and black participants. The average BMI was above the desirable range (20)(21)(22)(23)(24)(25), and the mean waist circumferences were greater than the cutoffs used to indicate risk of metabolic syndrome (94 cm in men and 80 cm in women). Female and male participants had a 6% and 10% risk of having a clinical cardiovascular event (nonfatal and fatal) over the next 10 y on the basis of the QRISK2 algorithm (www.qrisk.org).…”
Section: Resultsmentioning
confidence: 80%
“…About one-fifth of the study population was nonwhite, with similar proportions of Asian and black participants. The average BMI was above the desirable range (20)(21)(22)(23)(24)(25), and the mean waist circumferences were greater than the cutoffs used to indicate risk of metabolic syndrome (94 cm in men and 80 cm in women). Female and male participants had a 6% and 10% risk of having a clinical cardiovascular event (nonfatal and fatal) over the next 10 y on the basis of the QRISK2 algorithm (www.qrisk.org).…”
Section: Resultsmentioning
confidence: 80%
“…22 DHA supplementation reduced levels of TG in all 6 studies that considered healthy (nonvegetarian) individuals by approximately 2%-26%. [24][25][26][27][28][29][30][31][32] The largest decrease occurred in subjects with the highest baseline TG level (1.61 mmol/L, 143 mg/dL) or who received the largest dose of algal-DHA (6 g/d). In all but one study, 28 the level of HDL-C increased by 5%-9% but the change in LDL-C was inconsistent and not statistically significant.…”
Section: Plasma Lipids and Lipoproteinsmentioning
confidence: 99%
“…Evidence has also been presented [Byrne et al, 1998;Grainger et al, 2000] that TAG-rich lipoproteins sequester the active form of the atheroprotective cytokine TGF ␤ 1. High intakes of n-3 LCP ( 1 3 g/day) in the form of dietary supplements [Meydani, 2000;Vedin et al, 2008] decrease cytokine production and probably decrease inflammatory markers, but randomized controlled trials, using lower intakes as may habitually be consumed in usual diets, have failed to demonstrate any clear effects on cytokines, adhesion molecules or C-reactive protein [Blok et al, 1997;Balk et al, 2006;Theobald et al, 2007]. There is possible evidence that TFA increase systemic inflammation [Baer et al, 2004], but not all studies have consistently shown such effects [MotardBélanger et al, 2008].…”
Section: Inflammatory Markersmentioning
confidence: 99%